Exploring Aquaporins in Human Studies: Mechanisms and Therapeutic Potential in Critical Illness - Charikleia S. Vrettou; Vasileios Issaris; Stelios Kokkoris; Georgios Poupouzas; Chrysi Keskinidou; Nikolaos S. Lotsios; Anastasia Kotanidou; Stylianos E. Orfanos; Ioanna Dimopoulou; Alice G. Vassiliou (Life)
Aquaporins (AQPs) are membrane proteins facilitating water and other small solutes to be transported across cell membranes. They are crucial in maintaining cellular homeostasis by regulating water permeability in various tissues. Moreover, they regulate cell migration, signaling pathways, inflammation, tumor growth, and metastasis. In critically ill patients, such as trauma, sepsis, and patients with acute respiratory distress syndrome (ARDS), which are frequently encountered in intensive care units (ICUs), water transport regulation is crucial for maintaining homeostasis, as dysregulation can lead to edema or dehydration, with the latter also implicating hemodynamic compromise. Indeed, AQPs are involved in fluid transport in various organs, including the lungs, kidneys, and brain, where their dysfunction can exacerbate conditions like ARDS, acute kidney injury (AKI), or cerebral edema. In this review, we discuss the implication of AQPs in the clinical entities frequently encountered in ICUs, such as systemic inflammation and sepsis, ARDS, AKI, and brain edema due to different types of primary brain injury from a clinical perspective. Current and possible future therapeutic implications are also considered.